Relationship Between Religious Stereotypes, Religious Identity and Religious Tolerance - Павленко, Валентина Миколаївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article analyzes the concept of the stereotype of "sectarians" in Ukrainian society. It was shown that emotional and value assessment of "sectarians" is negative: they are disliked, disrespected, and avoided by others. The idea of representatives of non-traditional denominations as those who are actively trying to involve others in their views, meetings, communities, etc., is presented. It is also typical for society to perceive people who belong to non-traditional denominational groups as weak, insecure, dependent on the group leader, and so on. Peculiarities of religious identity and religious tolerance are studied: a fairly high level of religious tolerance in society has been confirmed, but there is a certain declarative identification with religious groups which is reflected, in particular, in the weakness of its manifestations at the behavioral level, in real religious life. It is proved that the general level of religious tolerance among the Orthodox, compared with atheists, is significantly higher: a more tolerant attitude is observed towards all religious groups, including "sectarians". There is also a significant difference in attitudes: Orthodox are more lenient with their "I", respect and value themselves more, while atheists are more critical of themselves. There are negative correlations between attitudes towards "sectarians" and certain characteristics of religious identity, in particular: the stronger the identification with one's religious group and the more a person likes his religious group, the worse the attitude towards "sectarians" is. However, the causal relationship, the real influence on the attitude towards "sectarians" is recorded only in one variable - the general level of religious tolerance: the higher the level of tolerance, the better the attitude towards those who are called "sectarians".